Polycystic Ovary Syndrome - treatment update - Marta Szymura; Marek Jarosław Molenda; Oliwia Brygida Woszczyńska; Paweł Maciej Rycąbel; Mateusz Romaniuk; Maria Wachowska; Mateusz Paniak; Agnieszka Ewelina Wojciechowska; Michał Brunon Krawczyk; Wojciech Jan Sowiński (Quality in Sport)
Introduction: